(untitled) (Journal of Universal Science Research, 2025)
This article explores the etymological and emotional-expressive aspects of achromatic colors, focusing on their semantic evolution, cultural significance, and lexical classification in Karakalpak and English. The study highlights the challenges of categorizing color-denoting adjectives and examines how historical, cultural, and linguistic factors shape color perception.